2015
DOI: 10.1016/j.wavemoti.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Coupled mode theory for acoustic resonators

Abstract: We develop the effective non-Hermitian Hamiltonian approach for open systems with Neumann boundary conditions. The approach can be used for calculating the scattering matrix and the scattering function in open resonatorwaveguide systems. In higher than one dimensions the method represents acoustic coupled mode theory in which the scattering solution within an open resonator is found in the form of expansion over the eigenmodes of the closed resonator decoupled from the waveguides. The problem of finding the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 38 publications
1
73
0
Order By: Relevance
“…The Hamiltonian approach provides a bottom-up scheme to construct the scattering matrix of the system, which also highlights the essential features and limitations of coupled-mode theory for wave scattering in various photonic structures [9][10][11][12]. To some extent, this effective Hamiltonian approach can be considered an advanced form of the standard coupled mode theory, taking into account the dispersive properties of the channels [13]. Let us consider, to be specific, an optical scatterer described by the effective Hamiltonian 0 H , which is coupled to M propagating channels labeled by 1, 2, , pM = .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The Hamiltonian approach provides a bottom-up scheme to construct the scattering matrix of the system, which also highlights the essential features and limitations of coupled-mode theory for wave scattering in various photonic structures [9][10][11][12]. To some extent, this effective Hamiltonian approach can be considered an advanced form of the standard coupled mode theory, taking into account the dispersive properties of the channels [13]. Let us consider, to be specific, an optical scatterer described by the effective Hamiltonian 0 H , which is coupled to M propagating channels labeled by 1, 2, , pM = .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In our recent work Maksimov et al (2015) we showed that the approach known in quantum mechanics as formalism of the effective non-Hermitian Hamiltonian Dittes (2000); Pichugin et al (2001) could be adapted for solving hard-wall acoustic cavity-duct problem. The essential feature of the approach is that it allows to recover transmission spectra of open-boundary systems relying on the spectral properties of their closed counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…where is the third order Pauli matrix. In order to return the solution of (9) to the same frequency with (7) we can simply apply the complex conjugation operator. By doing so, we obtain that the system has two independent solutions at the same frequency.…”
Section: Formalizationmentioning
confidence: 99%